KEANEKARAGAMAN JENIS REPTIL DI LABORATORIUM LAPANG TERPADU, UNIVERSITAS LAMPUNG - Fatmawati, Nimas Ayu; Dewi, Bainah Sari; Rusita; Fitriana, Yulia Rahma; Febryano, Indra Gumay (JURNAL RIMBA LESTARI, 2021)
Reptiles are cold-blooded animals that need to be known and their evenness as an environmental bio-indicator. The purpose of the study was to determine the diversity of species and the diversity of reptiles. The research was conducted in December 2020-January 2021 at the Integrated Field Laboratory of the University of Lampung. The research data was collected using the Visual Encounter Survey (VES) method with a combination of the Time Search method. Then the results were analyzed quantitatively using the Shannon-Wiener diversity index and the type mapping index. The results showed that there were five types of reptiles observed, namely the wall lizard (Hemidactylus frenatus), garden lizard (Eutropis multifasciata), striped blackhead snake (Hemalopsis buccata), grass lizard (Takydromus sexlineatus) and welang snake (Bungarus candidus) in the medium category. This is because the habitat still has sufficient food availability, whereas since human activities the habitat has been slightly disturbed. In the third habitat, the distribution of reptiles is even and the distribution of reptile species is included in the category of stable community. The reptile species found were not different because the distance in the three habitats was not too far away which made it easier for the species to move around. The balance of the campus environment can be determined by monitoring and researching the existence of reptiles at the University of Lampung. In addition, other efforts to reduce hunting and illegal trade in reptiles provide protected status for reptile species.